Input Substitutability and Cross-Country Variation in Sectoral Linkages - Sinha, Rishabh (World Bank, Washington, DC, 2019)
Using panel data on input-output intensities and expenditure prices from 28 countries, this paper finds the elasticity of substitution across sectoral inputs to be less than one in each of the three broad sectors of the economy. Intermediates are most complementary in the production of services while it is easiest to substitute across intermediates in the production of agricultural goods. Differences in relative prices alone account for a non-trivial fraction of the cross-country variation in sectoral linkages. Abstracting from the price channel that allows for substitution across inputs in response to changes in relative prices delivers biased aggregate implications of changes in productivity and distortions.